2002
DOI: 10.2202/1542-6580.1000
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Autothermal Steam Methane Reforming in a Fluidized Bed Membrane Reactor

Abstract: Fluidized bed reactors for steam methane reforming, with and without immersed membrane surfaces for withdrawal of hydrogen, are modeled with oxygen added in order to provide the endothermic heat required by the reforming reactions. Porous alumina, palladium and palladium-coated high-flux tubes are investigated as separation materials, the latter two being permselective. Hydrogen yield and permeate hydrogen molar flow are predicted to decrease with increasing oxygen flow, and to increase with temperature. When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Figure 9 compares predictions from this model at different temperatures with the simulation results of Dogan et al, 9 who based their simulation on the twophase bubbling bed model, without allowance for axial dispersion. Their model also does not account for the influence of volumetric flow changes with reaction.…”
Section: Table 8 Comparison Of Exit Model Predictions For Base Condit...mentioning
confidence: 92%
See 1 more Smart Citation
“…Figure 9 compares predictions from this model at different temperatures with the simulation results of Dogan et al, 9 who based their simulation on the twophase bubbling bed model, without allowance for axial dispersion. Their model also does not account for the influence of volumetric flow changes with reaction.…”
Section: Table 8 Comparison Of Exit Model Predictions For Base Condit...mentioning
confidence: 92%
“…Figure 9. Predicted methane conversions at different reactor temperatures compared to other simulation results of Dogan et al9 for identical conditions given in Figure3and Tables 2-4 of Dogan et al9 …”
mentioning
confidence: 89%
“…Several reactor models (e.g. Abba et al, 2003;Chen et al, 2003;Dogan et al, 2003;Grace et al, 2001;Patil et al, 2007) have also been developed to simulate FBMR processes. Experimental studies in a commercial FBMR unit were reported by Chen et al (2007).…”
Section: Introductionmentioning
confidence: 99%
“…The autothermal reforming (ATR) is a concept of producing hydrogen with increasing interest in research and industry [2][3][4][5][6][7]. It is essentially a combination of endothermic steam-reforming (SR) process chemically expressed as both of which are themselves concepts of producing hydrogen gas.…”
Section: Introductionmentioning
confidence: 99%
“…Based upon theoretical calculations and through verification from many experiments, it has been established that the ATR combines the advantages of the two hydrogen producing concepts, with negligible disadvantages [3][4][5] like additional heating or cooling of the reactor. Moreover, because of prior experience in industrial applications, much work was done to improve the design and the performance of ATR-reactors.…”
Section: Introductionmentioning
confidence: 99%